2016
DOI: 10.1111/nyas.13040
|View full text |Cite
|
Sign up to set email alerts
|

Drugs, games, and devices for enhancing cognition: implications for work and society

Abstract: As work environments change, the demands on working people change. Cognitive abilities in particular are becoming progressively more important for work performance and successful competition in a global environment. However, work-related stress, performance over long hours, lack of sleep, shift work, and jet lag affect cognitive functions. Therefore, an increasing number of healthy people are reported to use cognitive-enhancing drugs, as well as other interventions, such as noninvasive brain stimulation, to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 254 publications
(390 reference statements)
0
23
0
Order By: Relevance
“…Current evidence indicates that some of the main reasons include achieving a competitive advantage at school, university or work and coping with the pressure to succeed; maintaining levels of attention and performance when sleep deprived or jet‐lagged; and improving task‐related motivation (e.g. for tasks that are difficult to get started or unappealing) (Sahakian and LaBuzetta, ; Sahakian et al , ; Brühl and Sahakian, ). In addition to improving academic results, some students also reported taking cognitive enhancers to maintain an adequate work‐life balance (Hildt et al , ).…”
Section: Pharmacological Cognitive Enhancement In Healthy Peoplementioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence indicates that some of the main reasons include achieving a competitive advantage at school, university or work and coping with the pressure to succeed; maintaining levels of attention and performance when sleep deprived or jet‐lagged; and improving task‐related motivation (e.g. for tasks that are difficult to get started or unappealing) (Sahakian and LaBuzetta, ; Sahakian et al , ; Brühl and Sahakian, ). In addition to improving academic results, some students also reported taking cognitive enhancers to maintain an adequate work‐life balance (Hildt et al , ).…”
Section: Pharmacological Cognitive Enhancement In Healthy Peoplementioning
confidence: 99%
“…In addition to improving academic results, some students also reported taking cognitive enhancers to maintain an adequate work‐life balance (Hildt et al , ). In the workplace, the data available indicate that healthy adults use cognitive enhancing drugs to face the ever‐increasing stress and demands of the work environment (Brühl and Sahakian, ). The German survey found that people particularly prone to using cognitive enhancers were those worried about their jobs, working at the limit of their capabilities, required not to show emotions or working in high‐pressure fields where small mistakes can have serious consequences (Kordt, ).…”
Section: Pharmacological Cognitive Enhancement In Healthy Peoplementioning
confidence: 99%
“…These include brain stimulation devices and cognitive training packages that are designed to improve neural circuitry leading to neuroplasticity. The clearest benefits found thus far are in depression (improvement in treatment‐resistant symptoms following transcranial magnetic stimulation) and schizophrenia (cognitive remediation of memory deficits) …”
Section: Restoring Cognitive Functionmentioning
confidence: 99%
“…Work‐related stress is the primary reason for healthy individuals using cognitive‐enhancing drugs; likewise, students report academic competition and amplified feelings of concentration and wakefulness as their top motivators for smart drug use . Modafinil produces cognitive‐enhancing effects in healthy individuals, mostly in higher executive functions such as planning and decision‐making.…”
Section: Enhancing Cognitive Functionmentioning
confidence: 99%
“…For example, Elon Musk has recently created a new venture for "devices that can be implanted in the human brain, with the eventual purpose of helping human beings merge with software and keep pace with advancements in artificial intelligence" [1]. Intellectual jobs competition may be higher than in the past as it seems that more and more white collars tend to use drugs to improve their intellectual job performance [2]. Doping in sport with drugs is also not new [3] but the Superhuman Sports Society [4], which has been created in 2015, even works towards enhancing human sporting abilities with virtual reality and exoskeletons.…”
Section: Introductionmentioning
confidence: 99%